The assessment of rehabilitation and psycho-sexual problems in patients who suffered from rectal cancer with stomas - Nowicki, Andrzej; Kula, Olimpia; Kula, Zbigniew; Rzepka, Katarzyna; Zegarski, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2011)
Background : Colorectal cancer is an important health problem in Poland as well as around the whole world. Radical or palliative treatment often requires making an artificial stoma in many patients. Aim of the study : To assess physical rehabilitation and psycho-sexual problems of patients with rectum cancer and stoma. Material and methods : 50 patients with stoma who had undergone surgery because of rectal cancer participated in this survey. The survey was performed in the Oncology Centre in Bydgoszcz in 2008. The questionnaire contains questions related to socio-demographic information, self-assessment about used physical rehabilitation and psycho-sexual feelings. Results : 28%, 34% and 28% of patients know the goals of rehabilitation before surgery and during the early and late period after surgery, respectively. Information regarding psychological and sexual help was given to 12 (24%) and 3 (6%) patients, respectively. Basic physical activity before surgery was declared by 30 patients (60%), physical activity was not changed in 22 (44%) after surgery. Changes in intimate life after colostomy under cessation of sexual relations were observed in 18 patients (36%). As many as 46 patients (92%) did not use any assistance from a psychologist or sexologist. Conclusions : In the peri-operative period physical rehabilitation as part of treatment of patients with colorectal cancer and stoma was not sufficient. Only a few patients used psycho-sexual rehabilitation; it was the most neglected element of rehabilitative treatment. Patients with the most severe disease feel resigned to their fate, fear of death as well as happiness that they can be alive.